Electricity for growth and jobs in Tunisia: Exploring the nuclear and renewable electricity options - Schmidt, Peter; Lilliestam, Johan; Fürstenwerth, Daniel; Battaglini, Antonella (Tunisia: Economic, political and social issues, 2012)
In order to continue its socio-economic development and to solve its probably most pressing problem, the unemployment, Tunisia needs economic growth. Many factors need to be fulfilled for this to happen, most of them are not easy to achieve. One of the most important factors is to make sure that the electricity supply keeps pace with economic activity -without electricity, growth, and consequently job creation, will be slowed down. Tunisia's present power system is almost exclusively based on fossil fuels, which are imported at an ever-increasing, over time possibly unsustainable, level. Hence, two alternative pathways to a continued and increased dependency on fossil fuels for power generation have emerged: nuclear and renewable power. In this chapter, these two alternatives are explored, discussed and compared with respect to their financial, technical and socio-economical impacts and viability. We look in detail at the issues of investment needs and feasibility, the fit of the options with the existing electricity infrastructure system, the effects on local industry and economy, and fulfilment of seawater desalination needs. We conclude that the nuclear option is hardly viable, as it constitutes too large an investment, its techno-economical characteristics do not fit the small Tunisian power system, and the socio-economic benefits of nuclear power are few. The prospects for renewables are better, although many significant challenges remain: as renewables projects are of a more decentralised nature, they are more attractive investments than nuclear power, the expansion plans are embedded in an international investment context, and they fit better with the existing power system. However, renewables are too expensive to be a real alternative to fuel desalinisation plants in the short term. Most importantly, a well-designed policy effort to support renewables holds the potential of significant job creation and the emergence of a new Tunisian industry, with strong positive socio-economic effects. © 2012 by Nova Science Publishers, Inc. All rights reserved.
CRIS-Team Scopus Importer:2023-06-14